IBM Hyper-Scale Manager for IBM Spectrum Accelerate family IBM XIV, IBM FlashSystem A9000 and A9000R, and IBM Spectrum Accelerate - Martinez, Lisa; Dufrasne, Bertrand (IBM Corporation, International Technical Support Organization, 2019)
This IBM® Redbooks® publication describes storage management functions and their configuration and use with the IBM Hyper-Scale Manager management graphical user interface (GUI) for IBM XIV® Gen3, IBM FlashSystem® A9000 and A9000R, and IBM Spectrum"!Accelerate software. The web-based GUI provides a revolutionary object-centered interface design that is aimed toward ease of use together with enhanced efficiency for storage administrators. The first chapter describes general features of the GUI and installation of the IBM Hyper-Scale Manager server. Subsequent chapters illustrate some typical GUI actions, among many other possibilities, to manage and configure the storage systems, to define security roles, and to set up multitenancy. For most of the GUI-based actions that are illustrated in this book, the corresponding XIV Storage System command-line interface (XCLI) commands are also shown. This edition applies to IBM Hyper-Scale Manager V5.4. IBM Hyper-Scale Manager based GUI information regarding host attachment and replication is covered in IBM FlashSystem A9000, IBM FlashSystem A9000R, and IBM XIV Storage System: Host Attachment and Interoperability, SG24-8368 and IBM FlashSystem A9000 and A9000R Business Continuity Solutions, REDP-5401. See also IBM HyperSwap and Multi-site HA/DR for IBM FlashSystem A9000 and A9000R, REDP-5434
"This edition applies to IBM FlashSystem A9000 and IBM FlashSystem A9000R with software Version 12.3 with IBM Hyper-Scale Manager V5.5"--Page 2 of cover. - Number on back cover: SG24-8376-03. - "Storage.". - Includes bibliographical references. - Online resource; title from cover (Safari, viewed September 27, 2019)
Keywords: Computer storage devices; Enterprise resource planning; Virtual storage (Computer science); Cloud computing; Ordinateurs; Mémoires; Progiciels de gestion intégrés; Ordinateurs; Mémoires virtuelles; Infonuagique